Philo of Alexandria : an exegete for his time - Borgen, Peder. (Novum Testamentum, Supplements, 1997)
Philo's writings are a comprehensive and important source of late Second Temple Judaism. This volume gives important insights into his exegetical works. The structure of the books and their exegetical ideas are seen here as being closely connected and his writings are analysed against the background of the history, variety and outlook of Alexandrian Jewry. Philo's exegesis is a meeting place between Jewish and Greek notions and ideas; tensions are reflected, such as those between particularism and universalism, between specific biblical and historical earthly events and general macro- and micro-cosmic principles, and between heavenly ascents and interpreted history and eschatology. In addition, glimpses are gained of community life in a Hellenistic Jewish community, especially of issues on the borderline between Jews and their non-Jewish surroundings. New Testament material illuminates Philo's broader Jewish context, and in turn Philo throws light on New Testament backgrounds.